Cross-species experiments reveal widespread cochlear neural damage in normal hearing - Hari M. Bharadwaj; Alexandra R. Hustedt-Mai; Hannah M. Ginsberg; Kelsey M. Dougherty; Vijaya Prakash Krishnan Muthaiah; Anna Hagedorn; Jennifer M. Simpson; Michael G. Heinz (Communications Biology, 2022)
Cross-species experiments on chinchillas and at-risk humans suggest cochlear synaptopathy from noise exposure and aging are widespread even among individuals with clinically normal hearing status.